(3GdEbJUGO GdSjGSjs - (3YHO Gddg(B, (3SGbhQs ((3GdLRGFQ(B:s (3OGQ GdYdhe(B,s, 2004)
(3jVe CgejI GdJMdjd GdEbJUGOj , CSGdjH GdEfJGL GdELJeGYjI , eOGQS GdJMdjd GdEbJUGOjs
(3GdeQGLY U(B.140s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdSjGSjs; (3GdJMdjd GdEbJUGOjs